2022
DOI: 10.1007/s00467-022-05483-8
|View full text |Cite
|
Sign up to set email alerts
|

Rates of idiopathic childhood nephrotic syndrome relapse are lower during the COVID-19 pandemic

Abstract: Background Infections are thought to be primarily responsible for triggering relapse in children with steroid-sensitive nephrotic syndrome (NS). The COVID-19 pandemic promoted physical distancing, facial mask wearing, and greater attention to infection-prevention measures resulting in decreased transmission of infections. We hypothesized there would also be a decreased rate of NS relapse during this period. Methods We conducted a single-center retrospective chart review of children with steroid-sensitive NS. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Surprisingly, we did not find a difference in incidence between the before and during pandemic INS cohorts in either region. This is in line with findings from Southern California where the number of new cases the year before the pandemic was similar to that of the first year of the pandemic [ 17 ]. No higher incidence during the repeated peaks or waves of Covid-19 related hospitalisations – and thus, SARS-CoV-2 burden – was observed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Surprisingly, we did not find a difference in incidence between the before and during pandemic INS cohorts in either region. This is in line with findings from Southern California where the number of new cases the year before the pandemic was similar to that of the first year of the pandemic [ 17 ]. No higher incidence during the repeated peaks or waves of Covid-19 related hospitalisations – and thus, SARS-CoV-2 burden – was observed.…”
Section: Discussionsupporting
confidence: 90%
“…During these periods of lockdown, study teams of the LEARNS (the Netherlands) and NEPHROVIR-3 (Paris area, France) trial noticed a decrease in the number of first onset INS, hypothesising that this may be due to less exposure to viral pathogens as a – desired – result of social distancing. This phenomenon has previously been suggested for relapse rate [ 17 19 ]. Therefore, the aim of this study is to compare the incidence of INS before (before March, 2020) and during (from March, 2020 to December, 2021) the Covid-19 pandemic in the Netherlands and the Paris area.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…[39][40][41][42] Additionally, observational studies reported reductions in the incidence and relapse of the nephrotic and nephritic syndrome amongst children. 43,44 The reasons behind the decrease in glucosuria remain largely unknown; however, changes in adiposity status may not be attributed to this decrease because the incidence rate of diabetes mellitus amongst Japanese children is very low, at 2-3 cases per 100 000 person-years, 45 making it improbable to be reflected in the current data. Alternatively, an increase in the consumption of instant and processed foods during the COVID-19 pandemic might explain the reduction in glucosuria amongst children.…”
Section: Discussionmentioning
confidence: 89%
“…These results are in line with the data presented by Harambat et al [ 20 ], who did not find any increase in the relapse rate during the first COVID-19 wave in a cohort of 111 INS children, when compared to the same period of the previous year [ 20 ]. Furthermore, Crane et al reported a statistically significant lower relapse rate during the pandemic as compared to the previous 5 years, speculating that this difference could be related to the decreased rates of viral infections [ 24 ].…”
Section: Discussionmentioning
confidence: 99%